1986
DOI: 10.2135/cropsci1986.0011183x002600050005x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Selection for Resistance to European Corn Borer in a Corn Synthetic and Correlated Effects on Agronomic Traits1

Abstract: The European corn borer (ECB) [Ostrinia nubilalis (Hübner)] is the most damaging corn (Zea mays L.) insect pest in the USA. Utilization of corn hybrids with reduced susceptibility to ECB is the most economical method of control. Iowa normally has two generations of ECB each season that coincide with two growth stages of the plant. Sources of resistance to both generations in one genotype are rare and additional sources are needed. Resistance to ECB is conditioned by several genes and is primarily additive in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 0 publications
3
39
1
1
Order By: Relevance
“…However when traits related to insect resistance, such as tunnel length or damage ratings, were the selection criteria, other authors have reported a decrease in grain yield (Klenke et al 1986;Nyhus et al 1989;Russell et al 1979;Sandoya et al 2008). The relationship between yield and resistance is poorly understood and our data indicate that both selection programs have managed yield genes independent of stalk resistance genes.…”
Section: Discussionmentioning
confidence: 62%
“…However when traits related to insect resistance, such as tunnel length or damage ratings, were the selection criteria, other authors have reported a decrease in grain yield (Klenke et al 1986;Nyhus et al 1989;Russell et al 1979;Sandoya et al 2008). The relationship between yield and resistance is poorly understood and our data indicate that both selection programs have managed yield genes independent of stalk resistance genes.…”
Section: Discussionmentioning
confidence: 62%
“…However, the effect of stemborer damage on grain yield is a complex interaction between the insect and the host plant, and expression of resistance varies depending on time of infestation (Alghali, 1985(Alghali, , 1987Jarvis et al, 1986;Klenke et al, 1986;Taneja and Nwanze, 1989;MacFarlane, 1990;Thome et al, 1994); interplant variation (Harris, 1962); recovery resistance; ability to withstand stemborer damage (Flattery, 1982); compensation in grain yield (Heinrich et al, 1983;van den Berg et al, 1990), or a combination of two or more of these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Selecting for yield under infestation would increase resistance and/or tolerance, depending on the mechanism working against corn borer attack. In addition, it would eliminate the risk of loosing yielding ability after selecting for insect resistance as some authors have reported (Russell et al, 1979;Klenke et al, 1986 andKlenke et al, 1988;Butrón et al, 2000 andButrón et al, 2002). This paper complements the information published on the differences among the European maize landraces of the EUMLCC for plant resistance measured as tunnel length in the stem and damage on the grain nonagrioides is the most abundant corn borer in Pontevedra, while European corn borer is predominant in Zaragoza (Malvar et al, 1993;Cordero et al, 1998).…”
Section: Introductionmentioning
confidence: 99%